My cat Isis - Austen, Catherine, 1965-; Egger, Virginie, 1966- (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2011)
A young boy compares his cat Isis to the Egyptian goddess of the same name.
3.6
K-3
K-3
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Cats -- Fiction; Picture books for children